2020
DOI: 10.1093/nar/gkaa040
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal tail of the yeast mitochondrial transcription factor Mtf1 coordinates template strand alignment, DNA scrunching and timely transition into elongation

Abstract: Mitochondrial RNA polymerases depend on initiation factors, such as TFB2M in humans and Mtf1 in yeast Saccharomyces cerevisiae, for promoter-specific transcription. These factors drive the melting of promoter DNA, but how they support RNA priming and growth was not understood. We show that the flexible C-terminal tails of Mtf1 and TFB2M play a crucial role in RNA priming by aiding template strand alignment in the active site for high-affinity binding of the initiating nucleotides. Using single-molecule fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 39 publications
6
35
0
Order By: Relevance
“…In the present study, we show that the DNA binding activity of the transcription factors is autoinhibited by their C-terminal tail regions prior to their association with the RNAP subunit. Both Mtf1 and TFB2M contain a flexible Cterminal tail region of 16 to 20 aa that we recently showed plays important roles in transcription initiation (3). The present study shows that the C-tail has additional roles in regulating the DNA binding activity of the free factors.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In the present study, we show that the DNA binding activity of the transcription factors is autoinhibited by their C-terminal tail regions prior to their association with the RNAP subunit. Both Mtf1 and TFB2M contain a flexible Cterminal tail region of 16 to 20 aa that we recently showed plays important roles in transcription initiation (3). The present study shows that the C-tail has additional roles in regulating the DNA binding activity of the free factors.…”
Section: Discussionsupporting
confidence: 52%
“…During our studies of the C-terminal deletion mutants of Mtf1 (3), we stumbled upon a new finding that suggested that the flexible C-terminal tail of Mtf1 has an autoinhibitory function in DNA binding. Both Mtf1 and TFB2M contain a flexible Ctail region consisting of 16 to 20 aa, which we recently showed plays a critical role in template strand alignment including supporting high affinity binding of the initiating nucleotide for efficient RNA priming reaction (3). The 16 aa of the Mtf1 C-tail were not resolved in the crystal structure (9), whereas in the crystal structures of TFB2M, the fully or partially resolved Ctail region was found to be in different conformations (8).…”
Section: Mitochondrialmentioning
confidence: 93%
See 1 more Smart Citation
“…3C), and at a critical length of RNA, the C-tail will be displaced out from the active-site cavity. Single-molecule FRET studies show that IC to EC transition completes at 8-mer RNA synthesis and C-tail deletion delays the transition (14,15). Superposition of y-mtIC on POLRMT EC with 9-bp RNA:DNA (16) shows that C-tail must exit for IC to EC transition ( Fig.…”
mentioning
confidence: 99%
“…Biochemical studies show that the MTF1 C-tail plays an important role in template alignment, DNA scrunching, and triggering transition into elongation (15). The IC structure captures the entire C-tail in the active-site cavity and interacts with the template DNA, NTloop, and 5'-end of the RNA transcript.…”
mentioning
confidence: 99%